REAKSI PASAR MODAL INDONESIA SEBELUM DAN SESUDAH RESHUFFLE KABINET 12 AGUSTUS 2015 (EVENT STUDY PADA SAHAM ANGGOTA LQ 45 TAHUN 2015) - MUSYARROFAH, ATIQOTUL (Jurnal Akuntansi AKUNESA, 2016)
ABSTRACT Cabinet reshuffle carried out by President Jokowi-JK on August 12, 2015. Jokowi replaced five ministers were three of them were ministers in the economy. The reaction of society which reflects the expectations can be seen from the movement of stock prices in the Indonesian stock market. The market reaction is indicated by the presence or absence of difference of abnormal return, trading volume activity and security return variability. Data analysis is done by using paired sample t-test on abnormal return and the Wilcoxon signed rank test on trading volume activity and security return variability. The results show that there is difference in abnormal return, trading volume activity, and security return variability before and after of the cabinet reshuffle Jokowi JK August 12, 2015.Keywords: cabinet reshuffle, abnormal return, trading volume activity and security return variability